Validation and Comparison of Formol and FT-IR Methods for Assimilable Nitrogen in Vine Grapes - Skoutelas, D.; Ricardo-da-Silva, J.M.; Laureano, O. (South African Journal of Enology and Viticulture, 2011)
In this study, two methods used to evaluate assimilable nitrogen in grape juice were compared, namely: the formol method and the FÎ¿urier-transform mid-infrared (FT-MIR) spectroscopy. At the outset the formol method was validated in the laboratory by determining parameters such as precision, accuracy and trueness. Parallel recovery studies were conducted with a model solution and natural grape juice for ammonium and arginine. Average recoveries of ammonium for the formol titration ranged from 77% to 88% and for arginine from 90% to 97%. The repeatability and the intra laboratory reproducibility were ±6.4 and ±31.7 (mg/L of nitrogen) respectively. Formol titration was used as the reference method for the calibration of FT-MIR spectroscopy to determine the assimilable nitrogen in grape juice. Grape juice samples (n=71) for 7 red and 7 white varieties from the Lisbon region in Portugal were analyzed simultaneously by using the formol method and FÎ¿urier-transform mid-infrared (FT-MIR) spectroscopy. The results of this study demonstrated that it is possible to explore the applicability of FT-ÎœIR technology to detect the assimilable nitrogen in grape juice for quantification purposes. The correlation coefficient (R2=0. 993), standard prediction error (SEP; 6.4 mg/L) and the RPD or standard deviation of the data/ standard error of prediction value (Sd/Se; 7.8) proved satisfactory for the calibration of the instrument. In addition, the results obtained by FT-MIR spectroscopy were comparable to those obtained when using the reference method.